Comprehensive physiological, transcriptomic, and metabolomic analyses reveal the synergistic mechanism of Bacillus pumilus G5 combined with silicon alleviate oxidative stress in drought-stressed Glycyrrhiza uralensis Fisch. - Ma, Xin; Xu, Zhanchao; Lang, Duoyong; Zhou, Li; Zhang, Wenjin; Zhang, Xinhui (Frontiers in Plant Science, 2022)
Glycyrrhiza uralensis Fisch. is often cultivated in arid, semi-arid, and salt-affected regions that suffer from drought stress, which leads to the accumulation of reactive oxygen species (ROS), thus causing oxidative stress. Plant growth-promoting bacteria (PGPB) and silicon (Si) have been widely reported to be beneficial in improving the tolerance of plants to drought stress by maintaining plant ROS homeostasis. Herein, combining physiological, transcriptomic, and metabolomic analyses, we investigated the response of the antioxidant system of G. uralensis seedlings under drought stress to Bacillus pumilus (G5) and/or Si treatment. The results showed that drought stress caused the overproduction of ROS, accompanied by the low efficiency of antioxidants [i.e., superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), the ascorbate (AsA)–glutathione (GSH) pool, total carotenoids, and total flavonoids]. Inversely, supplementation with G5 and/or Si enhanced the antioxidant defense system in drought-stressed G. uralensis seedlings, and the complex regulation of the combination of G5 and Si differed from that of G5 or Si alone. The combination of G5 and Si enhanced the antioxidant enzyme system, accelerated the AsA–GSH cycle, and triggered the carotenoid and flavonoid metabolism, which acted in combination via different pathways to eliminate the excess ROS induced by drought stress, thereby alleviating oxidative stress. These findings provide new insights into the comparative and synergistic roles of PGPB and Si in the antioxidant system of plants exposed to drought and a guide for the application of PGPB combined with Si to modulate the tolerance of plants to stress.